2018
DOI: 10.1097/pr9.0000000000000700
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing chronic pain in late adolescence and early adulthood: prescription opioids, marijuana use, obesity, and predictors for greater pain interference

Abstract: Introduction:Chronic pain in late adolescence and young adults is understudied and poorly characterized.Objectives:We sought to characterize key variables that may impact pain interference in late adolescents and young adults with chronic pain, including prescription opioid use, marijuana use, psychological symptoms, and obesity.Methods:Retrospective, cross-sectional medical chart review for patients aged 17 to 23 years (N = 283; 61% Females) seeking care at a tertiary care pain clinic. Data on pain characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 38 publications
(45 reference statements)
0
17
0
Order By: Relevance
“… 31 , 85 In addition, in a review of tertiary pain clinic patients' medical charts, women reported more pain locations than men. 3 …”
Section: Resultsmentioning
confidence: 99%
“… 31 , 85 In addition, in a review of tertiary pain clinic patients' medical charts, women reported more pain locations than men. 3 …”
Section: Resultsmentioning
confidence: 99%
“…74 Hence, exposure to chronic pain during the sensitive adolescent period 75 may interfere with adaptive neuro-cognitive development (e.g., acquisition of self-regulatory skills) and social maturation (e.g., independence), making adolescents more susceptible to prolonged emotional difficulties and at its worst suicidality. 28,75 However at the same time, adolescents are shielded from some of the harsher socioeconomic effects of chronic disabling pain that may be experienced in adulthood (e.g., inability to work), and they are likely to be living in a social context which provides support for daily tasks. These highly speculative hypotheses await further scrutiny, and a systematic exploration of developmental similarities and differences underpinning the pain-suicidality association in adolescents and adults is warranted to tailor early interventions to patients' needs.…”
Section: Discussionmentioning
confidence: 99%
“…22,26 However, the manifestation of pain may vary between adolescents and adults, 21,27 and its effects may be particularly detrimental in adolescence, particularly by interfering with the adaptive development during this critical period. 28 Given the growing support for a relationship between pain and suicidality in adults (see Racine 13 , Rizvi et al 14 and Tang et al 15 ), establishing whether a similar relationship exists in adolescents has the potential to enhance our understanding of the interplay between physical and mental suffering in this age group, and to inform the development of prevention strategies. 6,29 In this paper, we report the findings of a systematic review designed to synthesise and critically evaluate the existing empirical evidence for an association between pain and suicidality in adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…Poor access to care for youth living with chronic pain has been identified as a longstanding problem and research priority for patients and families 7,10 . If healthcare services or care delivery are compromised, youth with pain are at risk of developing mental health concerns (including post-traumatic stress disorder (PTSD), depression, anxiety and suicide), deteriorations in functioning, and substance use disorder 11,12 . Moreover, many youth living with pain have previously existing mental health co-morbidities which places them at even greater risk 13 .…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 10 If health care services or care delivery is compromised, youth with pain are at risk of developing mental health concerns (including posttraumatic stress disorder [PTSD], depression, anxiety, and suicide), deteriorations in functioning, and substance use disorder. 11 , 12 Moreover, many youth living with pain have previously existing mental health comorbidities, which places them at even greater risk. 13 Starting in mid-March 2020 when widespread public health restrictions began in Canada, young people with chronic pain and their families have faced many challenges as ambulatory chronic pain programs halted new in-person consults, follow-up appointments, and individual therapy sessions.…”
Section: Introductionmentioning
confidence: 99%